2022
DOI: 10.3390/pathogens11070765
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Diagnostic Potential of a Commercial Cat Interferon Gamma Release Assay for the Detection of Mycobacterium bovis Infection in African Lions (Panthera leo)

Abstract: Mycobacterium bovis (M. bovis) infection in wildlife, including lions (Panthera leo), has implications for individual and population health. Tools for the detection of infected lions are needed for diagnosis and disease surveillance. This study aimed to evaluate the Mabtech Cat interferon gamma (IFN-γ) ELISABasic kit for detection of native lion IFN-γ in whole blood samples stimulated using the QuantiFERON® TB Gold Plus (QFT) platform as a potential diagnostic assay. The ELISA was able to detect lion IFN-γ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This study demonstrated that existing assays, previously evaluated for TB diagnosis in African lions ( 12 , 16 , 18 , 31 ) and cheetahs ( 13 ), showed potential for detecting M. bovis -infected leopards. The GXU ® was able to detect MTBC DNA in all five culture positive leopards that were tested, providing rapid results in a significantly shorter time than mycobacterial culture.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…This study demonstrated that existing assays, previously evaluated for TB diagnosis in African lions ( 12 , 16 , 18 , 31 ) and cheetahs ( 13 ), showed potential for detecting M. bovis -infected leopards. The GXU ® was able to detect MTBC DNA in all five culture positive leopards that were tested, providing rapid results in a significantly shorter time than mycobacterial culture.…”
Section: Discussionmentioning
confidence: 63%
“…Medians and inter-quartile ranges are indicated by horizontal bars. The lion assay cut-off value (33 pg/ml) is shown as a dotted line on the y-axis ( 18 ). There was a statistically significant difference between the test results (p = 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations